Dietary patterns and gestational hypertension in nulliparous pregnant Chinese women: A CONSORT report. Issue 29 (17th July 2020) - Chen, Xiaoju; Ding, Yiling; Shi, Lei; Wu, Dongcai; Wang, Li; Chen, Fangrong; Mo, Yuqiao
Abstract : Abstract: It has been well established that dietary patterns play important roles in the pathogenesis and development of hypertension. Our aim was to investigate the association between pregnancy dietary patterns and the risk of hypertension among nulliparous pregnant Chinese women. A cross-sectional, case-control study. Three hospitals in Haikou, the capital of Hainan Province, South China. A total of 2580 participants who reported dietary intake using a validated food frequency questionnaire (FFQ). Four primary dietary patterns were identified by principal component factor analysis and labeled as traditional Chinese, animal food, Western food, and salty snacks patterns. Women with high scores on pattern characterized by salty snacks were at increased risk. This study suggests that dietary pattern characterized by salty snack increases the risk of hypertension during pregnancy.